2008
DOI: 10.1097/prs.0b013e3181706ff2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Pelvic Ring with Vascularized Double-Strut Fibular Flap following Internal Hemipelvectomy

Abstract: Use of a vascularized double-strut fibular bone flap for pelvic ring reconstruction is effective in facilitating early ambulation and restoring normal to near-normal gait in patients undergoing internal hemipelvectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…Furthermore, there is no reconstruction of the abductor muscles to allow for better function of the hip. Some authors have described constructs using strut grafts [1,2], vascularized iliac pedicles [11], or vascularized fibulas [4,15,20] to connect remaining periacetabular bone to the sacrum. Although these techniques address the problems produced by not reconstructing the pelvis they have tended to be technically challenging, can result in high complication rates, and may not provide reliable union [2,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is no reconstruction of the abductor muscles to allow for better function of the hip. Some authors have described constructs using strut grafts [1,2], vascularized iliac pedicles [11], or vascularized fibulas [4,15,20] to connect remaining periacetabular bone to the sacrum. Although these techniques address the problems produced by not reconstructing the pelvis they have tended to be technically challenging, can result in high complication rates, and may not provide reliable union [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…A Type I resection includes wide excision of a portion, or the entirety of, the ilium, and a Type I-S resection involves resection of a portion of the sacrum [9]. Many authors [1,2,4,11,15] have suggested different strategies to deal with the discontinuity of the pelvis. Some have forgone any reconstruction of Type I resections [2,8], leaving the pelvic ring in discontinuity.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,48,61 Autologous bony reconstruction of the pelvis using fibula has been described in the literature. 2,11,18,41,48 Yajima and Tamai reported 2 cases of pelvic reconstruction using double-strut vascularized fibula flaps. 59 Sakuraba et al 48 reported their experience with 5 cases of Type I and Type II hemipelvectomy defects that were reconstructed with double-barreled vascularized fibula flaps.…”
Section: 13mentioning
confidence: 99%
“…7,9,11,[14][15][16]20,24,30,39,48,61 Usually a free vascularized fibula flap is used. 7,11,48,61 Autologous bony reconstruction of the pelvis using fibula has been described in the literature. 2,11,18,41,48 Yajima and Tamai reported 2 cases of pelvic reconstruction using double-strut vascularized fibula flaps.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation